The Application of Gamification as a Strategy towards Customer Engagement and Customer Loyalty Factors on Gojek - Rachman, Arief; Hudrasyah, Herry (Journal of Business and Management, 2020)
Abstract: There is a new method of marketing for a company to compete in digital era which is gamification. Gamification means inserting a game experience in non-game context to create value for the customer. Gamification could create customer engagement and customer loyalty for business and to achieve the business’ goals. This study want to investigate the relation of gamification with customer engagement and customer loyalty on Gojek. This research is using online survey for gathering the data from 232 respondents in Bekasi and Jakarta and the data will be analyse using PLS- SEM. Based on the findings, gamification is having a correlation towards customer engagement and customer loyalty on Gojek. The relationship between gamification and customer engagement are strong means gamification is an effective strategy to increase customer engagement, meanwhile relationship of customer engagement and customer loyalty are weak, so as gamification and customer loyalty means gamification is not always an effective strategy to create customer loyalty. It also concluded that rewards, challenges and points are the important gamification elements. Moreover, it is advised for the company to improve gamification elements as it to retain the engagement and loyalty for the customer and to support the gamification program with other marketing strategy.Keywords: Gamification, Customer Engagement, Customer Loyalty, Gojek.